Conceptualizing the impact of leader-member Exchange in non-profit and religious organisations: the case of waqf institutions in Malaysia / Sharfizie Mohd Sharip, Marinah Awang and Ramlee Ismail. - Mohd Sharip, Sharfizie; Awang, Marinah; Ismail, Ramlee (Universiti Teknologi Mara Selangor, 2019)
While a great discussion on past research done to investigate the impact on Leader-Member Exchange (LMX) in producing the positive outcome of the management, relatively little research has been done conducted to examine the link between LMX to the effectiveness of the management particularly in a religious based non-profit organization in a Malaysia setting. Meanwhile, a discussion on LMX of the non-profit organisation is not explicitly religious based as the discussion on Malaysia institution, and specifically among non-profit organisation religious based is lacking. Thus, the objective of this study to address the issue of communication among leader-member via LMX theory and to propose potential effect to the effectiveness of the management particularly in a religious based non-profit organisation, specifically in Waqf institutions in the Malaysian setting.